2000
DOI: 10.1016/s0029-7844(00)00788-2
|View full text |Cite
|
Sign up to set email alerts
|

A survey of pessary use by members of the american urogynecologic society

Abstract: While there are identifiable trends in pessary use, there is no clear consensus regarding the indications for support pessaries compared with space-filling pessaries, or the use of a single pessary for all support defects compared with tailoring the pessary to the specific defect. Randomized clinical trials are needed to define optimal pessary use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 16 publications
1
115
1
2
Order By: Relevance
“…Three other studies have evaluated pessary fitting; these previous studies reported successful fitting rates ranging from 56 to 64 % [9][10][11], which are slightly lower than our rate of 67 %. Fitting success may depend upon preconceived patient ideas, and both beliefs and attitudes regarding the etiology and success of pessary treatment might influence treatment choice [3,[12][13][14]. All treatment options should be discussed, and patients should actively participate in the treatment decision-making process.…”
Section: Reasons For the High Success Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Three other studies have evaluated pessary fitting; these previous studies reported successful fitting rates ranging from 56 to 64 % [9][10][11], which are slightly lower than our rate of 67 %. Fitting success may depend upon preconceived patient ideas, and both beliefs and attitudes regarding the etiology and success of pessary treatment might influence treatment choice [3,[12][13][14]. All treatment options should be discussed, and patients should actively participate in the treatment decision-making process.…”
Section: Reasons For the High Success Ratementioning
confidence: 99%
“…Pessary use is an excellent conservative treatment option for some patients with POP. A survey conducted by the American Urogynecologic Society reported that nearly two thirds of physicians would choose the vaginal pessary over surgery as the first-line treatment for this condition [3]. Pessaries can be categorized into the following two types: support and space-occupying.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The use of pessaries is common; more than 85% of gynecologists 9 and nearly 98% of urogynecologists prescribe them. 10 They provide anatomic support and can be used as a treatment of choice or in those who decline surgery (e.g., women who plan future childbearing, require temporary relief of prolapse while waiting for surgery or during pregnancy, or do not want surgical repair 11,12 ). Pessaries have few complications, although some authors suggest that they require lifestyle modification, 13,14 and the variety of shapes and sizes available affords choice and individual fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Pessary use is an excellent conservative treatment option for some POP patients. A survey conducted by the American Urogynecologic Society has reported that nearly two-thirds of physicians would choose a vaginal pessary over surgery as the first-line treatment for this condition [3]. Modern silicone pessaries come in a variety of types and sizes.…”
Section: Introductionmentioning
confidence: 99%